Clinical Characteristics of Patients Carrying the Q703K Variant of the NLRP3 Gene: A 10-year Multicentric National Study. - Naselli, Aldo; Penco, Federica; Cantarini, Luca; Insalaco, Antonella; Alessio, Mariolina; Tommasini, Alberto; Maggio, Cristina; Obici, Laura; Gallizi, Romina; Cimmino, Marco; Signa, Sara; Lucherini, Orso Maria; et al. (J Rheumatol, 2016)
OBJECTIVE: The aim of our study was to analyze the clinical and functional effect of the p.Q703K (p. Q705K, c. 2107C>A) variant of the NLRP3 gene in a population of patients screened for suspected cryopyrin-associated periodic syndrome (CAPS). METHODS: Since 2002, 580 patients underwent molecular analysis for NLRP3. Data on clinical presentation, response to treatment, and longterm followup were collected using a uniform questionnaire. The pattern of cytokine secretion after lipopolysaccharide stimulation from isolated monocytes was analyzed in 3 patients carrying the p.Q703K variant and 1 patient with a chronic infantile neurologic, cutaneous, articular syndrome phenotype carrying both the p.M406I and p.Q703K, and compared with 7 patients with CAPS with sure pathogenic variants and 6 healthy controls. RESULTS: The p.Q703K variant was found in 57 screened patients with an overall allelic frequency of 5%. The frequency in normal controls was 5.5%. Clinical data at the moment of molecular analysis and at followup were available in 36 patients. Two patients displayed additional mutations of NLRP3. The mean followup was 2.5 years. Thirteen patients (39%) had a final diagnosis different from the original suspicion of CAPS. The remaining 21 patients displayed a mild phenotype mainly characterized by recurrent episodes of urticarial rash and arthralgia. Only 8 patients were treated with anti-interleukin (IL)-1 treatment, with a complete response in 5 patients. The pattern of secretion of IL-1β and other cytokines (IL-6 and IL-1 receptor antagonist) in patients did not display the aberrancies observed in patients with CAPS and was similar to that observed in healthy controls. CONCLUSION: The present study confirms the weak clinical and functional effect of the p.Q703K variant.